Accessing bilingual code-switching competence - Jacqueline Toribio, Almeida (The international journal of bilingualism : cross-disciplinary, cross-linguistic studies of language behavior, 2001)
The present work is inspired by an interest in the syntactic regularities that underlie language alternations in Spanish-English bilingual speech, and the methodologies that may prove most reliable and informative in this exploration. Accordingly, it attends to the conceptual and methodological issues that must be addressed and surmounted, and taking account of these concerns, presents new methodologies for gathering codeswitching data. The robust findings attest to the validity of the methodologies and of the elicited data, affording a valuable source of facts for further research.